Activation of Protein Kinase C-α and Src Kinase Increases Urea Transporter A1 α-2, 6 Sialylation - Li, Xuechen (J Am Soc Nephrol, 2015)
The urea transporter A1 (UT-A1) is a glycosylated protein with two glycoforms: 117 and 97 kD. In diabetes, the increased abundance of the heavily glycosylated 117-kD UT-A1 corresponds to an increase of kidney tubule urea permeability. We previously reported that diabetes not only causes an increase of UT-A1 protein abundance but also, results in UT-A1 glycan changes, including an increase of sialic acid content. Because activation of the diacylglycerol (DAG)-protein kinase C (PKC) pathway is elevated in diabetes and PKC-α regulates UT-A1 urea transport activity, we explored the role of PKC in UT-A1 glycan sialylation. We found that activation of PKC specifically promotes UT-A1 glycan sialylation in both UT-A1-MDCK cells and rat kidney inner medullary collecting duct suspensions, and inhibition of PKC activity blocks high glucose-induced UT-A1 sialylation. Overexpression of PKC-α promoted UT-A1 sialylation and membrane surface expression. Conversely, PKC-α–deficient mice had significantly less sialylated UT-A1 compared with wild-type mice. Furthermore, the effect of PKC-α–induced UT-A1 sialylation was mainly mediated by Src kinase but not Raf-1 kinase. Functionally, increased UT-A1 sialylation corresponded with enhanced urea transport activity. Thus, our results reveal a novel mechanism by which PKC regulates UT-A1 function by increasing glycan sialylation through Src kinase pathways, which may have an important role in preventing the osmotic diuresis caused by glucosuria under diabetic conditions.